Cost effectiveness of the Oregon quitline "free patch initiative". (29th November 2007) - Fellows, Jeffrey L; Bush, Terry; McAfee, Tim; Dickerson, John
Abstract : Objective: We estimated the cost effectiveness of the Oregon tobacco quitline's "free patch initiative" compared to the pre-initiative programme. Methods: Using quitline utilisation and cost data from the state, intervention providers and patients, we estimated annual programme use and costs for media promotions and intervention services. We also estimated annual quitline registration calls and the number of quitters and life years saved for the pre-initiative and free patch initiative programmes. Service utilisation and 30-day abstinence at six months were obtained from 959 quitline callers. We compared the cost effectiveness of the free patch initiative (media and intervention costs) to the pre-initiative service offered to insured and uninsured callers. We conducted sensitivity analyses on key programme costs and outcomes by estimating a best case and worst case scenario for each intervention strategy. Results: Compared to the pre-intervention programme, the free patch initiative doubled registered calls, increased quitting fourfold and reduced total costs per quit by 2688. We estimated annual paid media costs were 215 per registered tobacco user for the pre-initiative programme and less than 4 per caller during the free patch initiative. Compared to the pre-initiative programme, incremental quitline promotion and intervention costs for the free patch initiative were 86 (range 22–353) per life year saved. Conclusions: Compared to the pre-initiative programme, the free patch initiative was a highly cost effective strategy for increasing quitting in the population.